In vitro Response of Human Mesenchymal Stromal Cells to Titanium Coated Peek Films and Their Suitability for Magnetic Resonance Imaging. Issue 5 (May 2015) - Elschner, Cindy; Noack, Carolin; Preißler, Carolin; Krause, Andreas; Scheler, Ulrich; Hempel, Ute
Abstract : Medical imaging is an important tool for the post-operative checkup of an accurate position of an implant as well as for monitoring the integration in the adjacent tissue that may influence the success of a medical device. Unfortunately, the possibility to use imaging methods is associated with the implant material and all the established metallic materials for surgery do not show a proper "imaging compatibility". The present study is a combined investigation of the in vitro response to human mesenchymal stromal cells (hMSC) and magnetic resonance imaging (MRI) compatibility of the potential material combination polyetheretherketone/titanium (PEEK/Ti) for medical devices. Because of the advantageous imaging properties and the mechanical and chemical stability, PEEK becomes more and more an alternative to common metallic implant materials like titanium or cobalt‒chrome. However, PEEK is a bioinert material having a limited ability for direct bone incorporation. Due to its excellent biocompatibility, Ti was chosen as coating material to enhance the cellular response. The result is a combination with advantageous properties: the magnetic susceptibility and elastic modulus close to bone, corrosion resistance and mechanical flexibility of PEEK and the excellent biocompatibility of titanium. The appearance of metal-related artifact was discussed in electrical resistivity and magnetic susceptibility. Therefore, two titanium coatings have been investigated: a complete coating and a structured surface avoiding surface conductivity. To determine the in vitro biocompatibility, the cell responses were assessed in terms of the overall morphology of the hMSC and their cell area distribution, proliferation, osteogenic differentiation and mineral deposition. The cellular stress was evaluated by the prostaglandin E2 level. The bonded materials both produced no disturbing artifacts in magnetic resonance imaging. Compared to the pure PEEK material, the titanium coated specimens showed an enhanced biocompatibility, which is indicated by a higher cell number, larger activity of the enzyme tissue non-specific alkaline phosphatase and therefore a greater amount of deposited calcium and phosphate. The results on bare PEEK are accompanied with a higher cellular stress level, which is indicated by prostaglandin E2 . Highlights: The possibility to use medical imaging is associated with the implant material. The evaluation of implant materials should include their imaging properties. Ti coating on PEEK enhanced the in vitro response to hMSC. Ti coating of 50 nm thickness produced no imaging artifact. PEEK/Ti is a potential bonded material for medical devices.